Pendidikan Islam dalam Tinjauan Ontologi, Epistemologi, dan Aksiologi - Khomsatun, Novi (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2019)
This study discusses the Islamic education in reviews of ontology, epistemology, andaxiology. The third review was to discuss education with different viewpoints basedon the object of study. Islamic education in terms of ontology focuses on Islamiceducational philosophy which objected in science. Islamic education in terms ofepistemology focuses on the source of origin of the science. While Islamic educationin terms of its axiology is viewing of science usefulness for life.